2018
DOI: 10.1515/auto-2017-0123
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable machine learning with reject option

Abstract: Classification by means of machine learning models constitutes one relevant technology in process automation and predictive maintenance. However, common techniques such as deep networks or random forests suffer from their black box characteristics and possible adversarial examples. In this contribution, we give an overview about a popular alternative technology from machine learning, namely modern variants of learning vector quantization, which, due to their combined discriminative and generative nature, incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…( 36) does, but is easier to optimize overhowever, note that by using a surrogate instead of the original constraint Eq. (36) we give up closeness which, in our opinion, would be acceptable if the solutions stay somewhat close to each other 6 . We try out and compare both approaches in the experiments (see Section 4).…”
Section: Distance To Decision Boundarymentioning
confidence: 67%
See 1 more Smart Citation
“…( 36) does, but is easier to optimize overhowever, note that by using a surrogate instead of the original constraint Eq. (36) we give up closeness which, in our opinion, would be acceptable if the solutions stay somewhat close to each other 6 . We try out and compare both approaches in the experiments (see Section 4).…”
Section: Distance To Decision Boundarymentioning
confidence: 67%
“…At the same time, RelSim gets close to 0 if the sample is far away -i.e. both distances are large [6].…”
Section: Reject Optionsmentioning
confidence: 93%
“…the classifier outputs a specific warning in the case of outliers or settings close to a decision boundary. It has recently been shown that such technology can mediate the problem of adversarial examples for some intuitive classifiers [28]. It remains a matter of research in how far this technology can also improve security for deep neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…KMeans-Proxy. Through observations on our generalizability results, we present a simple 'reject option' [4,15,16] for fake news detectors, called KMeans-Proxy. KMeans-Proxy is based on KMeans clustering, and is inspired by research into proxy losses [30,47] and foundation models [3,7,33].…”
Section: Introductionmentioning
confidence: 99%